A prospective case series of Fournier's gangrene at a tertiary centre involving adjacent organs. Issue 12 (14th June 2021) - David, Rowan; Traeger, Luke; Kahokehr, Arman; Miller, John; Ashrafi, Akbar
Abstract: Background: Recent studies of patients with Fournier's gangrene (FG) highlight the importance of early surgical intervention in improving mortality rates. We prospectively determined subgroups of patients with FG at high risk of severe local morbidity. Methods: We prospectively evaluated all patients diagnosed with FG at a tertiary hospital (1 January 2018 to 1 January 2021). Data were collated on demographics, comorbidity, infection source, treatment and clinical outcomes. Results: We identified 14 consecutive male patients with a median (interquartile range) age of 57 (50–64) years. Most common risk factors were diabetes ( n  = 10, 71%) and obesity ( n  = 10, 71%). Median (range) HbA1c was 11.20 (7.5–15.3), and body mass index of 41.25 (23.7–70.0). Seven patients had adjacent organ involvement (AOI), involving the corporal bodies (57%) and testes (43%). The most common suspected source was dermatological (50%), followed by genitourinary (29%) and gastrointestinal (GI) (21%). Median (interquartile range) hospital length of stay (LOS) was 32 (8.5–30.75) days. Patients with AOI were more likely to have a suspected GI source, need mechanical ventilation ( p  = 0.023), a significantly longer LOS ( p  = 0.015) and time to wound closure ( p  = 0.04). Patients with suspected dermatological origin of infection, had a significantly lower rate of AOI ( p  = 0.029), mechanical ventilation ( p  = 0.029) and a shorter LOS ( p  = 0.035). Conclusion: In our prospective series, FG is associated with a high rate of AOI and suspected non‐dermatological origin of infection, which confers significant perioperative morbidity including the need for mechanical ventilation, LOS and longer time from initial debridement to wound closure. Abstract : This prospective series of patients diagnosed with Fournier gangrene at a tertiary hospital demonstrated a higher rate of adjacent organ involvement and non‐dermatological origin of infection than the currently published literature. Fournier gangrene patients with adjacent organ necrosis and suspected non‐dermatological origin of infection were associated with significant perioperative morbidity, including increased duration of mechanical ventilation, length of stay and time from initial debridement to wound closure.